2020
DOI: 10.1523/jneurosci.1166-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Network Coupling Enables Efficient Task Performance without Local Task-Induced Activations

Abstract: Neurobehavioral studies in humans have long concentrated on changes in local activity levels during repetitive executions of a task. Spontaneous neural coupling within extended networks has latterly been found to also influence performance. Here, we intend to uncover the underlying mechanisms and the interaction with task-induced activations. We demonstrate that high performers in visual perception and motor sequence tasks present an absence of classical task-induced activations, but, instead, strong spontaneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Aligned with our hypothesis, we found that lower anticipatory a FSS was associated with greater efficiency. We do not believe this finding is at odds with studies showing that frontoparietal a synchronization, in contrast to desynchronization, is associated with top-down control, since a synchronization is predominantly observed during resting wakefulness (Sadaghiani et al, 2012;Allaman et al, 2020) and in poststimulus evoked activity, particularly for attended stimuli Michalareas et al, 2016;Lobier et al, 2018). Indeed topdown control via a oscillations is suggested to be flexible, with synchronization observed during internal processing/rest, and desynchronization prevailing during anticipatory task preparation (Palva and Palva, 2007;Klimesch, 2012).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Aligned with our hypothesis, we found that lower anticipatory a FSS was associated with greater efficiency. We do not believe this finding is at odds with studies showing that frontoparietal a synchronization, in contrast to desynchronization, is associated with top-down control, since a synchronization is predominantly observed during resting wakefulness (Sadaghiani et al, 2012;Allaman et al, 2020) and in poststimulus evoked activity, particularly for attended stimuli Michalareas et al, 2016;Lobier et al, 2018). Indeed topdown control via a oscillations is suggested to be flexible, with synchronization observed during internal processing/rest, and desynchronization prevailing during anticipatory task preparation (Palva and Palva, 2007;Klimesch, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…We hypothesized desynchronization of anticipatory FSS as it has been related to cortical disinhibition, signifying increased excitability to facilitate the processing of impending stimuli (Haegens et al, 2011;Wang et al, 2016). Notably, frontoparietal a synchronization, i.e., network coupling has also been associated with top-down control, but this occurs in contexts different from phasic stimulus anticipation, i.e., during resting wakefulness (Sadaghiani et al, 2012;Allaman et al, 2020) and in poststimulus sensory evoked activity Michalareas et al, 2016;Lobier et al, 2018). Indeed a oscillations show flexible signatures, with greater synchronization during internal task-related processing and rest, but desynchronization during preparation for upcoming task-relevant information (Palva and Palva, 2007;Klimesch, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Here, instead of a concern with changes in neural activity "triggered" by external events, the focus is on intrinsic physiological features, such as functional connectivity, power or phase-coupling of frequency-specific oscillations (e.g., alpha rhythm 3 ). The putative cognitive role of these features are sometimes inferred based on their relationship to behavioural or psychological measures 3,4 , or by evaluating an anatomical overlap with task evoked activity patterns reported in other studies 5,6 . This approach aims to find a correspondence between intrinsic and task evoked neural patterns (sometimes termed the brain's 'functional architecture') 7 .…”
Section: A Dichotomy In Human Neurosciencementioning
confidence: 99%
“…Interestingly, resting state source-space phase-coupling and amplitude-coupling constitute spatially distinct associations with behavioural task performance (Guggisberg et al, 2015). Further, resting state e-phys connectivity not only predicts individuals' perceptual performance but also stimulus-related activation (oscillation power) on tasks (Allaman et al, 2020).…”
Section: Association Of Resting State Activity and Connectivity With Behavioural Traits Across Individualsmentioning
confidence: 99%